Pengurangan Kadar Amonia dari Limbah Cair Pupuk Urea dengan Proses Adsorpsi menggunakan Adsorben Bentonit - Hasbun Kosim; Susila Arita; Hermansyah Hermansyah (Faculty of Mathtmatics and Natural Sciences, 2015)
The Liquid waste of the urea fertilizer plant was caused by the inefficiency of urea manufacturing process and amonia plant equipment, urea, and packaging section. Inefficiency in equipment was due to that the age of equipment was relatively old, damages in treatment and inaccurate process that resulted ammonia exposed along the river so that it could finally pollute water biota. The research was conducted through adsorption process using bentonite adsorbent which was initially physically activated to open external porosity, so that the ammonia absorption became bigger. The adsorption process was conducted in jar test by using lab scale under the following process and treatment condition: determine the stirring used from 100-200rpm, adsorbent mass 10-40 gram/200 ml, heating temperature 100-1400C. The results of the research showed that the percentage of the highest ammonia concentration reduction in solution waste was 82,05% which was obtained in bentonite activation temperature 1200C, absorbent mass 38 g/200 ml, stirring in 100 rpm and contact time in 60 minutes.